A method for constructing a quantitative structure-activity relationship model of a cyclodextrin polymer modified zero-valent iron material

CN122907199APending Publication Date: 2026-10-13DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611092755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,柔性环糊精聚合物制备反应为剧烈放热过程,所得材料的结构往往具有高度变异性,重现性差,限制了材料构效关系的探究

Benefits of technology

[0008]本发明的有益效果:本发明综合考虑环糊精种类、柠檬酸与环氧氯丙烷的摩尔比、环糊精聚合物与铁的质量比、铁盐前驱体的种类等制备参数,以及环糊精聚合物及其改性零价铁材料在水中的溶胀率等结构特性,构建了环糊精聚合物改性零价铁材料的活化氧化性能的定量构效关系模型,该模型具有良好的预测性能,对环糊精聚合物改性零价铁材料的定制和优化应用具有指导意义。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907199A_ABST
    Figure CN122907199A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of environmental remediation materials, and discloses a construction method of a quantitative structure-activity relationship model of a cyclodextrin polymer modified zero-valent iron material. In view of the unclear structure-activity relationship of the cyclodextrin polymer modified metal material, the preparation parameters and structural characteristics of the material are comprehensively considered, a quantitative structure-activity relationship model of the activation and oxidation performance of the cyclodextrin polymer modified zero-valent iron material is constructed, and it is proved that the quantitative structure-activity relationship model has good prediction ability, and has guiding significance for customization and optimization application of the cyclodextrin polymer modified zero-valent iron material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental remediation materials technology, and relates to a method for constructing a quantitative structure-property relationship model of cyclodextrin polymer-modified zero-valent iron materials. Background Technology

[0002] Water pollution has become one of the most serious challenges of the 21st century. A large number of organic pollutants, including conventional and emerging pollutants such as polycyclic aromatic hydrocarbons (PAHs), phenols, benzene compounds, pesticides, and antibiotics, have been detected in the aquatic environment. These pollutants are mostly persistent, bioaccumulative, and toxic, posing a serious threat to surface water and groundwater. Due to the matrix effect prevalent in polluted water bodies, natural water components often compete with target pollutants for adsorption sites and / or consume oxidants, leading to a rapid decline in the efficiency of existing adsorption and oxidation treatment technologies. Cyclodextrin polymer-modified metal materials are a promising class of adsorbents and / or catalysts in advanced oxidation processes, thanks to the molecular recognition properties of cyclodextrin cavities, which give these materials high selectivity and stability in water. These materials are typically constructed using cyclodextrin polymers (CDPs) as carriers for metal particles. Therefore, a deep understanding of the structure-property relationships of cyclodextrin polymer-modified metal materials is crucial for the customization and application optimization of novel water purification materials.

[0003] Rigid cyclodextrin polymers are mainly synthesized through nucleophilic aromatic substitution reactions between rigid crosslinking agents (such as tetrafluoroterephthalonitrile) and the hydroxyl groups of cyclodextrin. Patent CN112427021 A uses tetrafluoroterephthalonitrile as a crosslinking agent, and mixes β-cyclodextrin, tetrafluoroterephthalonitrile and magnetic iron nanoparticles in a mass ratio of (15~25):10:(0.25~2.5) in a solution of potassium carbonate, anhydrous tetrahydrofuran and anhydrous N,N-dimethylformamide for crosslinking polymerization. After reacting at 85°C for 1~2 days, a magnetic nanoparticle-cyclodextrin composite adsorbent is obtained. Patent CN109331793 A uses tetrafluoroterephthalonitrile as a crosslinking agent. A crosslinking polymerization reaction is carried out in a solution of potassium carbonate, tetrahydrofuran, and anhydrous N,N-dimethylformamide at a molar ratio of 2:(0.7~1.1) using tetrafluoroterephthalonitrile and β-cyclodextrin, reacting at 82~90℃ for 40~60 hours to obtain a cyclodextrin polymer. Subsequently, a mixture of the cyclodextrin polymer, ferrous salt, ferric salt, and sodium hydroxide at a mass ratio of 0.1:(0.05~0.07):(0.13~0.19):(4~6) is added to water to load magnetic iron particles. The reaction is carried out at 85~95℃ for 20~30 hours to obtain a magnetic cyclodextrin polymer adsorbent (the entire preparation process takes approximately 60~90 hours). However, the rigid crosslinking agent has significant steric hindrance and weak reactivity, resulting in long preparation cycles, low material yields, and small-scale production of rigid cyclodextrin polymers and their metal composites. Currently, there are few reports on the effects of preparation conditions on the structure or properties of rigid cyclodextrin polymer-modified nanomaterials.

[0004] Flexible cyclodextrin polymers can be rapidly prepared within hours through non-selective crosslinking polymerization of cyclodextrin with flexible crosslinking agents (such as epichlorohydrin (EPI) and ethylenediaminetetraacetic acid (EDTA)). Among these, flexible cyclodextrin polymers prepared using epichlorohydrin as a crosslinking agent have received the most attention in the field of modified nanomaterial development due to their high reactivity, simple preparation, and low cost. Patent CN104475749 B discloses a method for preparing β-cyclodextrin-stabilized encapsulated nano-zero valent iron. Using epichlorohydrin as a crosslinking agent, under nitrogen protection, 0.2 g of nano-zero valent iron, 6.0 g of β-cyclodextrin, and 15 mL of 40% sodium hydroxide solution are added to a 250 mL three-necked flask, and the mixture is reacted in a 60°C water bath for 0.5–1 hour to obtain black β-cyclodextrin-stabilized encapsulated nano-zero valent iron. Patent CN 114100331 B uses epichlorohydrin as a crosslinking agent. 100g of β-cyclodextrin is added to 400g of a 1% sodium hydroxide solution, and 120g of epichlorohydrin is added dropwise in an oil bath at 50°C. The reaction is then rapidly carried out at 80°C for 1 hour to obtain a cyclodextrin polymer. Subsequently, acid-hydrolyzed titanium tetrachloride and the cyclodextrin polymer are reacted at 80°C for 1 hour to obtain a cyclodextrin polymer-metal composite material. However, the preparation reaction of the flexible cyclodextrin polymer is a violently exothermic process, and the structure of the resulting material often exhibits high variability and poor reproducibility, limiting the exploration of the structure-property relationship of the material.

[0005] To achieve structural optimization applications of cyclodextrin polymer-modified metallic materials, this invention constructs a quantitative structure-activity relationship (QSAR) model for the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron (ZVI) materials. Based on the cyclodextrin polymer-confined ZVI synthesis method proposed in our 2025 paper (Cyclodextrin polymer-confined synthesis of new nZVI activators for enhanced persulfate oxidation of organic contaminants in water, Journal of Environmental Management, 396(2025), 128131), dozens of structurally diverse cyclodextrin polymer-modified ZVI materials were controllably prepared by changing the type of cyclodextrin, the ratio of crosslinking agent to cyclodextrin, the ratio of shearing agent to crosslinking agent, temperature, stirring rate, the ratio of cyclodextrin polymer to iron, and the type of iron salt precursor. Based on the material preparation parameters and structural characteristics, a QSAR model for the activation and oxidation properties of cyclodextrin polymer-modified ZVI materials was constructed. This invention provides guidance for the customization and application optimization of cyclodextrin polymer-modified ZVI materials. Summary of the Invention

[0006] To address the current lack of clarity regarding the structure-activity relationship (SOR) of cyclodextrin polymer-modified metal materials, this invention comprehensively considers the material preparation parameters and structural characteristics to construct a quantitative SOR model for the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials, guiding material customization and application optimization. The technical solution of this invention is as follows: A method for constructing a quantitative structure-property relationship model for cyclodextrin polymer-modified zero-valent iron materials, comprising the following steps: (1) Preparation of zero-valent iron materials modified by cyclodextrin polymers; Based on the method of cyclodextrin polymer-confined synthesis of new nZVI activators for enhanced persulfate oxidation of organic contaminants in water, Journal of Environmental Management, 396(2025), 128131, proposed in our 2025 paper, we prepared 28 structurally diverse cyclodextrin polymer-modified zero-valent iron materials. A variety of structurally diverse cyclodextrin polymer-modified zero-valent iron materials were prepared by changing the following conditions in the zero-valent iron synthesis method: Cyclodextrins include one of the following: α-CD, β-CD, γ-CD, and HP-β-CD; Molar ratio M of epichlorohydrin to cyclodextrin EPI:CD =15~35; The molar ratio M of citric acid to epichlorohydrin CA:EPI =0.0~0.1; The temperature is 50~100℃; The stirring speed is 300~1000 rpm; The mass ratio of cyclodextrin polymer to iron m CDP:Fe =0.5~20; The types of iron salt precursors are divalent iron salts or trivalent iron salts; among them, the divalent iron salt is one of FeCl2, FeCl2•4H2O and FeSO4•7H2O, and the trivalent iron salt is one of FeCl3 and FeCl3•6H2O; (2) Construction of a quantitative structure-activity relationship model for the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials; Apparent rate constant of persulfate degradation of naphthalene in water activated by cyclodextrin polymer-modified zero-valent iron materials k obsThe natural logarithm of the equation was used as the dependent variable Y, and the following variables were used as independent variables X1 to X7: type of cyclodextrin, molar ratio of citric acid to epichlorohydrin, mass ratio of cyclodextrin polymer to iron, type of iron salt precursor, swelling rate of cyclodextrin polymer in water, and swelling rate of cyclodextrin polymer-modified zero-valent iron material in water. Finally, a quantitative structure-activity relationship model for the activation and oxidation performance of cyclodextrin polymer-modified zero-valent iron material was obtained by fitting the model. Among them, the type of cyclodextrin is represented by the cavity size and number of hydroxyl groups of the cyclodextrin. The quantitative structure-activity relationship model is expressed as follows:

[0007] Where Y represents the apparent rate constant of the degradation of naphthalene in water by cyclodextrin polymer-modified zero-valent iron material activating persulfate. k obs The natural logarithm of ln(min) is expressed in units of ln(min) -1 X1 is the cavity size of the cyclodextrin, in nm; X2 is the number of hydroxyl groups in the cyclodextrin; X3 is the molar ratio of citric acid to epichlorohydrin; X4 is the mass ratio of the cyclodextrin polymer to iron; X5 is the valence of the iron salt precursor; X6 represents the swelling rate of the cyclodextrin polymer-modified zero-valent iron material in water, in g / g; X7 represents the swelling rate of the cyclodextrin polymer in water, in g / g.

[0008] The beneficial effects of this invention are as follows: This invention comprehensively considers preparation parameters such as the type of cyclodextrin, the molar ratio of citric acid to epichlorohydrin, the mass ratio of cyclodextrin polymer to iron, and the type of iron salt precursor, as well as structural characteristics such as the swelling rate of cyclodextrin polymer and its modified zero-valent iron material in water, and constructs a quantitative structure-activity relationship model for the activation and oxidation performance of cyclodextrin polymer modified zero-valent iron material. This model has good predictive performance and provides guidance for the customization and optimized application of cyclodextrin polymer modified zero-valent iron material. Attached Figure Description

[0009] Figure 1 This is a comparison chart of predicted and measured values ​​from a quantitative structure-activity relationship model of the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials.

[0010] Figure 2 This is a graph showing the degradation effect of a customized cyclodextrin polymer modified with zero-valent iron material to activate persulfate on typical organic pollutants in natural water. Detailed Implementation

[0011] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0012] Example 1: Construction of a quantitative structure-property relationship model for cyclodextrin polymer-modified zero-valent iron materials; Using naphthalene (a key pollutant) as a model compound, the apparent rate constant of naphthalene degradation in water by cyclodextrin polymer-modified zero-valent iron materials was determined. k obs The naphthalene content was mainly obtained through a batch degradation experiment. The naphthalene degradation experiment was conducted in a 40 mL glass bottle with a total reaction solution volume of 30 mL. The experimental conditions were: material dosage 0.1 g / L, persulfate concentration 1 mmol / L, naphthalene concentration 10 mg / L, shaking rate 180 rpm, and reaction temperature 25℃. At pretreatment intervals (2, 5, 10, 15, 25, 40, and 60 minutes), samples were drawn using a 1 mL syringe, filtered through a 0.22 μm PTFE membrane filter, and then transferred to an autosampler vial (2 mL) for high-performance liquid chromatography (HPLC) analysis. Furthermore, the cyclodextrin content of the cyclodextrin polymer-modified zero-valent iron material was determined using the phenol-sulfuric acid colorimetric method, the iron content was determined using the o-phenanthroline spectrophotometric method, and the swelling rate of the cyclodextrin polymer and its modified zero-valent iron material in water was measured by gravimetric method.

[0013] Using cyclodextrin polymer-modified zero-valent iron materials to activate persulfate degradation of naphthalene in water k obs The natural logarithm of the variable is used as the dependent variable Y, and the preparation parameters of cyclodextrin polymer-modified zero-valent iron materials (such as the type of cyclodextrin, the molar ratio of epichlorohydrin to cyclodextrin, etc.) are used. EPI:CD The molar ratio of citric acid to epichlorohydrin (M) CA:EPI Temperature, stirring rate, and mass ratio of cyclodextrin polymer to iron (m CDP:Fe The types of iron salt precursors and their structural characteristics (such as cyclodextrin content, iron content, and swelling ratio in cyclodextrin polymer-modified zero-valent iron materials) are used as independent variables X1~X2. i Incorporate into the multiple linear regression equation and eliminate P The optimal model (Equation 1) is obtained by identifying insignificant terms >0.05 and terms with high collinearity. The ln values ​​of the material are then simulated and calculated based on the regression analysis results. k obs The fitting results between the predicted and measured values ​​are shown in the figure. Figure 1 , model R 2 It is 0.801.

[0014] Where Y represents the apparent rate constant of the degradation of naphthalene in water by cyclodextrin polymer-modified zero-valent iron material activating persulfate. k obs The natural logarithm of ln(min) is expressed in units of ln(min) -1X1 is the cavity size of the cyclodextrin, in nm; X2 is the number of hydroxyl groups in the cyclodextrin; X3 is the molar ratio of citric acid to epichlorohydrin; X4 is the mass ratio of the cyclodextrin polymer to iron; X5 is the valence of the iron salt precursor; X6 represents the swelling rate of the cyclodextrin polymer-modified zero-valent iron material in water, in g / g; X7 represents the swelling rate of the cyclodextrin polymer in water, in g / g.

[0015] Example 2: Customized cyclodextrin polymer-modified zero-valent iron material with high activation and oxidation properties; Based on the quantitative structure-activity relationship model, HP-β-CD and ferric salts were selected as raw materials to prepare cyclodextrin polymer-modified zero-valent iron materials with high activation and oxidation properties. EPI:CD =15、M CA:EPI =0.0401, 65℃, 450rpm and m CDP:Fe Cyclodextrin polymer-modified zero-valent iron material was prepared under conditions of 2:1. This cyclodextrin polymer-modified zero-valent iron material exhibits a high iron content (24.8 wt%) and a moderate swelling ratio (3.5 g / g). Its activated persulfate has been used to measure and predict the effect of naphthalene in water. k obs The values ​​were 0.2553 min. -1 and 0.2637min -1 With an error of only 3.2%, this model demonstrates its accuracy in predicting the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials.

[0016] Example 3: Customized cyclodextrin polymer-modified zero-valent iron material with moderate activation and oxidation properties; Based on the quantitative structure-activity relationship model, α-CD and trivalent iron salts were selected as raw materials to prepare cyclodextrin polymer-modified zero-valent iron materials with moderate activation and oxidation properties. EPI:CD =20、M CA:EPI =0.0120, 85℃, 550rpm and m CDP:Fe Cyclodextrin polymer-modified zero-valent iron material was prepared under conditions of 5. This cyclodextrin polymer-modified zero-valent iron material has a moderate iron content (15.9 wt%) and a high swelling ratio (4.5 g / g). Its activated persulfate has been used to measure and predict the effect of naphthalene in water. k obs The values ​​were 0.1614 min. -1 and 0.1674min -1 With an error of only 3.6%, this model demonstrates its accuracy in predicting the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials.

[0017] Example 4: Customized cyclodextrin polymer-modified zero-valent iron material with low activation and oxidation properties; Based on the quantitative structure-activity relationship model, γ-CD and divalent iron salts were selected as raw materials to prepare cyclodextrin polymer-modified zero-valent iron materials with low activation and oxidation properties. EPI:CD =25、M CA:EPI =0.0093, 95℃, 650rpm and m CDP:Fe Cyclodextrin polymer-modified zero-valent iron material was prepared under conditions of 10. This cyclodextrin polymer-modified zero-valent iron material exhibits a low iron content (6.5 wt%) and a low swelling ratio (2.7 g / g). Its activated persulfate activity on naphthalene in water was measured and predicted. k obs The values ​​were 0.0425 min. -1 and 0.0407min -1 The deviation was only 4.4%, which demonstrates the accuracy of this model in predicting the activation and oxidation performance of cyclodextrin polymer-modified zero-valent iron materials.

[0018] Example 5: Customized highly active cyclodextrin polymer-modified zero-valent iron material activates the degradation of typical organic pollutants in natural water by persulfate; The degradation reaction was carried out in a 40 mL glass bottle, with a total reaction solution volume of 30 mL. First, 0.009 g of a customized highly active material was weighed into the glass tube. Then, 29 mL of a solution containing 1 mg / L naphthalene, toluene, carbamazepine, bisphenol A, atrazine, or imidacloprid was added. Finally, 1 mL of sodium persulfate stock solution (0.06 mol / L) was added to initiate the activation and degradation reaction. The reaction system consisted of collected natural water, and its chemical composition included Cl... - SO4 2- CO3 2- Mg 2+ Ca 2+ The concentrations of DOM were 84 mg / L, 75 mg / L, 112 mg / L, 36 mg / L, 77 mg / L, and 16 mg / L, respectively. The glass vials were placed in a shaker and reacted at 180 rpm and 25°C for 60 minutes. Samples were drawn using a syringe, filtered through a 0.22 μm PTFE membrane filter, and then transferred to a liquid chromatography vial for HPLC analysis. The results are as follows: Figure 2 As shown, in natural water, the material activated persulfate to achieve removal rates of 99%, 100%, 100%, 100%, 99%, and 96% for naphthalene, toluene, carbamazepine, bisphenol A, atrazine, and imidacloprid within 60 minutes, respectively. This result demonstrates the selectivity and stability of the customized highly active material in a real-world water matrix.

[0019] Example 6: Customized high-activity cyclodextrin polymer-modified zero-valent iron material activates the degradation of organic pollutants in groundwater by persulfate; The degradation reaction was carried out in a 40mL glass bottle, with a total reaction solution volume of 30mL. First, 0.024g of a customized highly active material was weighed into the glass bottle, then 29mL of toluene-contaminated groundwater was poured in, and finally 1mL of sodium persulfate stock solution (0.06mol / L) was added to initiate the activation and degradation reaction. The reaction system consisted of collected groundwater, whose main chemical components included toluene and Cl-. - SO4 2- CO3 2- Mg 2+ Ca 2+ The concentrations of DOM were 138 mg / L, 427 mg / L, 204 mg / L, 146 mg / L, 32 mg / L, 97 mg / L, and 193 mg / L, respectively. The glass vials were placed in a shaker and reacted at 180 rpm and 25°C for 60 minutes. Samples were drawn using a syringe and filtered through a 0.22 μm PTFE membrane filter, then transferred to a liquid chromatography vial for HPLC analysis. The customized highly active material activated persulfate achieved a 100% removal rate of toluene from groundwater within 60 minutes, demonstrating the material's selectivity and stability in a real-world aquatic matrix.

Claims

1. A method for constructing a quantitative structure-property relationship model for cyclodextrin polymer-modified zero-valent iron materials, characterized in that, The steps are as follows: (1) Preparation of zero-valent iron materials modified by cyclodextrin polymers; A variety of cyclodextrin polymer-modified zero-valent iron materials with diverse structures were prepared by a cyclodextrin polymer-confined zero-valent iron synthesis method. A variety of structurally diverse cyclodextrin polymer-modified zero-valent iron materials were prepared by changing the following conditions in the zero-valent iron synthesis method: Cyclodextrins include one of the following: α-CD, β-CD, γ-CD, and HP-β-CD; Molar ratio M of epichlorohydrin to cyclodextrin EPI:CD =15~35; The molar ratio M of citric acid to epichlorohydrin CA:EPI =0.0~0.1; The temperature is 50~100℃; The stirring speed is 300~1000 rpm; The mass ratio of cyclodextrin polymer to iron m CDP:Fe =0.5~20; The types of iron salt precursors are divalent iron salts or trivalent iron salts; among them, the divalent iron salt is one of FeCl2, FeCl2•4H2O and FeSO4•7H2O, and the trivalent iron salt is one of FeCl3 and FeCl3•6H2O; (2) Construction of a quantitative structure-activity relationship model for the activation and oxidation properties of cyclodextrin polymer-modified zero-valent iron materials; Apparent rate constant of persulfate degradation of naphthalene in water activated by cyclodextrin polymer-modified zero-valent iron materials k obs The natural logarithm of the equation was used as the dependent variable Y, and the following variables were used as independent variables X1 to X7: type of cyclodextrin, molar ratio of citric acid to epichlorohydrin, mass ratio of cyclodextrin polymer to iron, type of iron salt precursor, swelling rate of cyclodextrin polymer in water, and swelling rate of cyclodextrin polymer-modified zero-valent iron material in water. Finally, a quantitative structure-activity relationship model for the activation and oxidation performance of cyclodextrin polymer-modified zero-valent iron material was obtained by fitting the model. Among them, the type of cyclodextrin is represented by the cavity size and number of hydroxyl groups of the cyclodextrin. The quantitative structure-activity relationship model is expressed as follows: Where Y represents the apparent rate constant of the degradation of naphthalene in water by cyclodextrin polymer-modified zero-valent iron material activating persulfate. k obs The natural logarithm of ln(min) is expressed in units of ln(min) -1 X1 is the cavity size of the cyclodextrin, in nm; X2 is the number of hydroxyl groups in the cyclodextrin; X3 is the molar ratio of citric acid to epichlorohydrin; X4 is the mass ratio of the cyclodextrin polymer to iron; X5 is the valence of the iron salt precursor; X6 represents the swelling rate of the cyclodextrin polymer-modified zero-valent iron material in water, in g / g; X7 represents the swelling rate of the cyclodextrin polymer in water, in g / g.

Citation Information

Patent Citations

  • Preparation method of β-cyclodextrin stabilized embedded nano zero-valent iron

    CN104475749B

  • Magnetically crosslinked beta-cyclodextrin polymer adsorbent and preparation method thereof

    CN109331793A

  • Magnetic nanoparticle-cyclodextrin composite adsorbent as well as preparation method and application thereof

    CN112427021A

  • Volatile Organic Compound Treatment Materials, Preparation Methods and Applications

    CN114100331B